Overstayed Migratory Bird Species on The Coast of Banda Aceh City, Aceh Province - Yuri Gagarin; Abdullah Abdullah; Zulfikar Zulfikar; Hafizd Ramadhan (Universitas Islam Negeri Ar-Raniry, 2024)
Bird migration is a critical ecological phenomenon influenced by various factors such as temperature changes, food availability, and reproductive cycles. Understanding the dynamics of migratory bird populations within specific regions is essential for conservation efforts. This study aims to identify migratory bird species within Banda Aceh City, focusing on the phenomenon of overstaying migratory birds. Conducted between April and June 2022, data collection took place in several locations, employing the concentration count method. Descriptive data analysis was performed to catalog bird species, and the Shannon-Wiener index was utilized to assess biodiversity. Results revealed the presence of four shorebird species. The study underscores the importance of protecting migratory bird populations in urban environments and highlights the potential impacts of their loss or disruption. Joint conservation efforts are crucial to safeguarding these species, and favorable conditions may encourage some individuals from commonly migrating species to remain in urban areas.